Uncovering antidepressant prescription patterns: a three-year analysis of outpatient trends - Hossein Karami; Reza Mehrizi; Mohammad Effatpanah; Azamsadat Rivandi; Rajabali Daroudi; Nezam Armand; Leila Ghamkhar (BMC Psychiatry)
Abstract Background Antidepressants (ADs) are prescribed for various conditions, including neurological and rheumatoid diseases. This study aims to analyze ADs prescribing trends in Iranian outpatients over three years, with a focus on age, sex, and ADs class. Methods A retrospective cohort study was conducted using prescription data from the Iranian Health Insurance Organization (IHIO) between March 2021 and March 2024. The dataset included 8,924,431 prescriptions from 3,524,273 patients who received at least one ADs. ADs were classified into four groups: tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs), serotonin and norepinephrine reuptake inhibitors (SNRIs), and atypical ADs. The data were processed via the cross-industry standard process for data mining and analyzed using a multivariate logistic regression model. Results SSRIs were the most commonly prescribed class, accounting for 63.71% of prescriptions, with sertraline being the most common drug (24.65%). Females accounted for 66.11% of the patient population. ADs prescriptions increased with age, and females were more likely to receive TCAs and SNRIs than males, who had higher rates of atypical ADs use. Conclusions This study revealed a notable increase in ADs prescriptions in Iran, particularly among women and older individuals. Continued monitoring of ADs prescription is crucial for optimizing outcomes, especially for vulnerable groups such as elderly individuals.